Social Housing Leads to Increased Ethanol Intake in Male Mice Housed in Environmentally Enriched Cages - Fulenwider, Hannah D.; Robins, Meridith T.; Caruso, Maya A.; Ryabinin, Andrey E. (Frontiers in Behavioral Neuroscience, 2021)
An individual’s social environment affects alcohol intake. However, the complex interactions between social context and alcohol intake remain understudied in preclinical models. In the present study, we sought to characterize the effects of social housing on voluntary ethanol intake in male C567BL/6J mice using a continuous access two-bottle choice model. This was accomplished using HM2 cages, which allow for the continuous monitoring of individuals’ fluid intake through radiofrequency tracking while they remain undisturbed in a group setting. These cages are moderately environmentally enriched compared to standard shoebox cages. By analyzing the levels of voluntary ethanol intake between socially- and individually-housed mice in HM2 cages, we were able to parse apart the effects of environmental enrichment versus social enrichment. We found that while intake levels were overall lower than those observed when animals are singly housed in standard shoebox cages, socially-housed males consumed significantly more ethanol compared to individually-housed mice, suggesting that while environmental enrichment attenuates ethanol intake, social enrichment may, in fact, potentiate it. This effect was not specific for alcohol, however, in that ethanol preference did not differ as a product of social context. We also found that the total number of non-consummatory channel entries were consistently higher in individually-housed mice. A single corticotropin releasing factor receptor 1 antagonist treatment significantly decreased both water and ethanol intake in socially- and individually-housed mice up to 3hr post-treatment, though the effect on water intake was longer lasting. This treatment also significantly decreased the number of non-consummatory channel entries in individually-housed mice, but not in socially-housed mice, suggesting that increased channel visits may be a stress-related behavior. Lastly, we examined blood ethanol concentrations and FosB immunoreactivity to characterize the physiological responses to ethanol intake in socially- and individually-housed mice. The number of FosB-positive cells in the centrally-projecting Edinger-Westphal nucleus and nucleus accumbens shell positively correlated with average baseline ethanol intake in individually-housed mice, but not in socially-housed mice. Overall, we found that social, but not environmental, enrichment can increase ethanol intake in male C57BL/6J mice. Future studies need to test this phenomenon in female mice and assess the generalizability of this finding.